Environmental sustainability concerns - Mujibur Rahman, Md (Environmental Engineering Division : Centre for Environmental and Resource Management : International Training Network Centre, BUET, 2006)
Papers presented at the international symposium organised by Environmental Engineering Division and others, during 7-9 Feb. 2006, BUET, Dhaka.